The efficacy and mechanism of vonoprazan-containing triple therapy in the eradication of Helicobacter pylori - Zhang, Zinan; Liu, Fen; Ai, Feiyan; Chen, Xiong; Liu, Rui; Zhang, Chao; Fang, Ning; Fu, Tian; Wang, Xiaoyan; Tang, Anliu (Frontiers in Pharmacology, 2023)
Purpose: Vonoprazan (VPZ) produces a strong acid-inhibitory effect, which can potentially eradicate Helicobacter Pylori (H. pylori). We aimed to assess whether a 14-day VPZ-containing triple therapy was safe and effective in the Chinese population and the potential mechanism. Methods: Enrolled patients confirmed to be infected with H. pylori were randomly divided into four groups: VPZ+ doxycycline + furazolidone , VPZ + doxycycline + amoxicillin, esomeprazole (EPZ) + bismuth + doxycycline + furazolidone, and EPZ + colloidal bismuth + doxycycline + amoxicillin for 14 days. The eradication rate, medication adherence, and incidence of adverse events (AEs) were evaluated. Inhibition of H. pylori by VPZ and EPZ in vitro was assessed. H. pylori treated with appropriate concentrations of VPZ and EPZ were sequenced by transcriptome analysis to explore the antibacterial mechanism. Results: A higher eradication rate were observed in VPZ-containing triple therapy. No obvious differences were observed in medication adherence or the incidence of AEs. VPZ had no direct inhibitory effect on H. pylori, whereas EPZ directly inhibited H. pylori may through downregulated genes related to the ribosome. Conclusion: In the Chinese population, 14-day VPZ-containing triple therapy was safe and more effective and can be used clinically as first-line H. pylori treatment.